The Impact of the Jigsaw Type Cooperative Learning Model on Independent Learning and Social Studies Achievement - Ginanjar Pratama; Tirsa Christiani (Institute of Computer Science (IOCS), 2023)
This research delves into the impact of the Jigsaw Type Cooperative Learning Model on students' independent learning processes and social studies learning achievement. The study employs a quasi-experimental design, involving both experimental and control groups from middle and high school levels. The Jigsaw Type model, an extension of Elliot Aronson's original Jigsaw method, is implemented to assess its influence on collaborative learning, individual accountability, and academic outcomes. Quantitative data, including pre and post-assessment scores, are subjected to statistical analyses, revealing statistically significant improvements in social studies achievement within the experimental group. Concurrently, qualitative data derived from surveys, teacher observations, and student reflections highlight positive perceptions and collaborative dynamics during Jigsaw Type sessions. The findings suggest a positive correlation between the Jigsaw Type Cooperative Learning Model and enhanced social studies learning achievement. Additionally, the model demonstrates efficacy in fostering independent learning skills, emphasizing the importance of collaboration and autonomy in tandem. This research contributes to the existing literature by specifically examining the Jigsaw Type model within the context of social studies education. The study advances our understanding of the nuanced relationship between cooperative learning, individual autonomy, and academic success.